SISTEM JUAL BELI HANDPHONE DENGAN SKEMA KREDIT MENURUT TINJAUAN HUKUM EKONOMI SYARIAH - Yanti, Rahma; Bunyamin, Andi; Lawang, Hasanna; Raehana, Syarifa; Martini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of information technology has made mobile phones a vital necessity for the community, including in Topoyo City, Central Mamuju Regency. The high price of mobile phones has encouraged businesses to offer credit payment schemes as an alternative for consumers who cannot afford cash purchases. However, the practice of buying and selling mobile phones on credit has the potential to cause legal issues if not implemented in accordance with the principles of Sharia Economic Law. This study aims to determine the system of buying and selling mobile phones with a credit scheme implemented in Topoyo City and analyze its compliance with Sharia provisions. This study uses a qualitative method with a case study approach. Data were obtained through direct interviews with counter owners and consumers, supported by documentation and literature studies. The analysis was conducted descriptively by examining credit buying and selling practices based on the pillars, conditions, and principles of Islamic jurisprudence, particularly regarding the concepts of bai' al-taqsith and murabahah. The results show that credit transactions are carried out through direct agreements without a financing institution. The difference between the cash and credit prices is agreed upon at the beginning of the contract. However, weaknesses remain, such as the lack of a written contract and the potential imposition of late fees. According to sharia, this practice is permitted as long as it meets the principles of justice, transparency, and is free from usury, gharar, and dzulm.